Penelitian Islam: Dasar dan Filosofi - Marzuki, Marzuki (LP2M IAIN Palangka Raya, 2014)
This article is a continued understanding of some thoughts delivered by the Islamic study experts. Actually, Islamic study orientation is still floating and it does not have a clear goal. Some parts of Islamic study isÂ model or a similar effort done byÂ orientalists in studying Islam, and in line with the vision and the mission starting from false conclusion about Islam. Therefore, Islamic study experts in the earlier awakening of Islam such asÂ Al-banna, al-maududi, Ismail Raji al Faruqi, Ziauddin sardar, and Muhammad Naquib al-Attas have offered various thoughts in implementing the framework of Islamic study in line with the vision and the mission of Islam so that their mindset becomes the basis for development of Islamic study.